2010
DOI: 10.2478/s11686-010-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Bat flies from the deciduous Atlantic Forest in southern Brazil: Host-parasite relationships and parasitism rates

Abstract: This study describes the assemblage of ectoparasitic bat flies, their hosts, and parasitism rates in an Atlantic Forest area in southern Brazil. Bats were captured monthly for one year at two sites. We captured 95 bats belonging to nine species, but only Artibeus lituratus, Artibeus fimbriatus, Sturnira lilium (Phyllostomidae) and Myotis nigricans (Vespertilionidae) were found to be parasitized. The bat flies collected were: Streblidae -Paratrichobius longicrus (on A. lituratus) and Megistopoda aranea (on A. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…This abundance of both species and ectoparasites per host is opposed to the hypothesis that a higher mean intensity of ectoparasites would be a result of less competition for hosts by flies in areas with lower richness of ectoparasite species (Camilotti et al 2010). Probably, biogeographical and historical factors of host populations in each area, besides the number of species and individuals sampled, should also have their contribution in species number and intensity of infestation of ectoparasites.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…This abundance of both species and ectoparasites per host is opposed to the hypothesis that a higher mean intensity of ectoparasites would be a result of less competition for hosts by flies in areas with lower richness of ectoparasite species (Camilotti et al 2010). Probably, biogeographical and historical factors of host populations in each area, besides the number of species and individuals sampled, should also have their contribution in species number and intensity of infestation of ectoparasites.…”
Section: Discussionmentioning
confidence: 44%
“…Among factors that may attribute to the highest number of bat fly species found in the cerrado, we propose: 1) the study area's location near the Amazon eastern transition zone (Ab 'Saber 1977), which includes the distributional limit of various host species (Simmons 2005) that can support different component communities; 2) factors external to the host that can affect the abundance of ectoparasites and their hosts, such as the type of climate, vegetation (Prevedello et al 2005) or host shelter (Wenzel et al 1966, Patterson et al 2007; 3) the highest number of individuals and host species than those reported in other studies with less rich and abundant fauna, such as those conducted in deciduous forest (Camilotti et al 2010) and caatinga (Rios et al 2008), a result that could favor the sample of host species with different component communities as well as the finding of bat fly species that occur in low prevalence in their host species; 4) the major sampling effort that may contribute to the finding of more host species and individuals, which is comparable just to the realized in Atlantic forest by Bertola et al (2005, Unauthenticated Download Date | 5/11/18 9:56 PM 2011) -that had, at most, the half of the sampling effort of this study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Additionally, it is possible to find bat fly species that are of low prevalence on their host species, such as those reported in deciduous forests (Camilotti et al 2010) and the Caatinga (Rios et al 2008), who presented a less rich and abundant fauna. Santos et al (2013) listed were the vegetation structure, the abundance of host shelter and the high number of individuals and host species among the most important factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that bats having high infestation rates by bat flies use long-term roosts, while bats with low infestation use ephemeral ones (Wenzel andTipton 1966, Kunz 1982b). In the same study area, an investigation about the relationships between bats and ectoparasite bat flies revealed high rates of parasitism on A. fimbriatus and low rates of parasitism on A. lituratus (Camilotti et al 2010). Thus, in this area A. fimbriatus may use more durable and resistant roosts, such as caves and tree holes, while A. lituratus may use ephemeral roosts, such as canopy trees.…”
Section: Discussionmentioning
confidence: 99%